The internalization of Value in Thematic Learning Scientific Nuances by Primary Teacher Education - Tahmid Sabri (JPDI (Jurnal Pendidikan Dasar Indonesia), 2018)
Internalizing the value of character in primary school children is fundamental, but the reality in school teachers is still difficult to do because of the inappropriateness of the approach used. The solution needs to be addressed by a scientific approach so that this study is expected to describe the design of learning to its implementation. This research uses the method of description through class action done by students peer teaching fellow colleagues. The findings show that the design of value internalization in scientific learning can be done well by the students from the mapping of themed concepts and sub-themes to the determination of KI, KD, Indicator, objective formulation, activities, and integrated evaluation of attitudes, skills, and knowledge in an integrated manner. Similarly, the well-packed implementation of the initial activity, the core activities to the final activity, it looks the scientific nuances that deliver the internalization of values on the participants of learning that will personally on themselves as individuals who are pious, noble, intelligent, skilled, creative , discipline, independence, responsibility and democratic. This achievement cannot be separated from the various obstacles experienced by students but can be overcome, so as not to reduce the acquisition of expected learning outcomes. The results of this study are expected to be used as a basic capital for the development of thematic learning either for the needs of students who are teaching in elementary school or for the development of integrated therapeutic learning in elementary school.